Sistem Penunjang Keputusan Sistem Operasi Untuk Layanan E-Mail Server Dengan Pendekatan Analytical Heirarchy Proses (AHP) - Ita Erliyani; Siti Maesaroh; Widiya Sapitri (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2020)
In the world of IT technology is growing rapidly, with the rapid development of these specialized companies engaged in the procurement of bandwidth must always conduct searches about IT technology in the field of network services. And the flow of highly needed data or information exchange continues to increase, one of which is via e-mail. In small companies that do not have their own e-mail server or email server backup, they look for services to hosting, network or service companies engaged in data services. Therefore PT NAP Info Lintas Nusa wishes to improve services by adding new services, namely the Email server service. This service is intended for companies that do not have their own e-mail server or companies that want to back up their e-mail. In this case PT NAP Info Lintas Nusa does not yet have specific criteria to determine what operating system will be used that can support the running of the service. So the company decided to use the AHP method with expert choice to determine what criteria would be chosen so as to determine the alternative to be chosen.